Alcuni spunti di riflessione sui primi anni dell’Analisi collettiva: 1975-1981 - Righetti, Valentino (Il sogno della farfalla, 2026)
The aim of this article is to highlight some aspects that allow to understand the importance of the theoretical framework of Massimo Fagioli, composed by the volumes Istinto di morte e conoscenza, La marionetta e il burattino, and Teoria della nascita e castrazione umana, in the inception and development of the psychotherapeutic practice known as Collective Analysis. Such psychoterapeutic practice has been fundamental in the training of hundreds of psychotherapists who currently operate within this theoretical approach. The article traces key milestones in the early history of the Collective Analysis from 1975 to 1981, including significant moments in the author’s life.